Elevated F‐EDN correlates with mucosal eosinophil degranulation in patients with IBS—A possible association with microbiota?. Issue 3 (21st June 2021) - Casado‐Bedmar, Maite; de‐Faria, Felipe Meira; Biskou, Olga; Lindqvist, Carl Mårten; Ranasinghe, Purnika Damindi; Bednarska, Olga; Peterson, Christer; Walter, Susanna A.; Carlson, Marie; Keita, Åsa V.
Abstract: Eosinophils have been linked to functional dyspepsia; however, less is known about their role in irritable bowel syndrome (IBS). This study tested the hypothesis of alterations in levels of fecal eosinophil‐derived neurotoxin (F‐EDN) and eosinophil density and degranulation within the colonic mucosa of IBS patients compared with healthy controls (HC). Colonic biopsies were collected from 37 IBS patients and 20 HC and analyzed for eosinophil numbers and local degranulation of eosinophil cationic protein (ECP) by histologic procedures. Fecal samples were collected for F‐EDN and microbiota analysis. Differentiated 15HL‐60 cells were used in vitro to investigate the direct effect of live bacteria on eosinophil activation measured by a colorimetric assay with o‐phenylenediamine (OPD) substrate. We observed a higher number of eosinophils and increased extracellular ECP in the mucosa of IBS patients compared with HC. Moreover, F‐EDN levels in IBS samples were elevated compared with HC and positively correlated to extracellular ECP. Metagenomic analysis showed significant correlations between bacterial composition and eosinophil measurements in both HC and IBS patients. In vitro experiments revealed an increased degranulation of 15HL‐60 after stimulation with Salmonella typhimurium, Salmonella enterica, and Yersinia enterocolitica . To conclude, we could demonstrate alterations related to eosinophils in IBS, and, for the first time, a positive correlation between F‐EDN levels and degranulated eosinophils in the colonic mucosa of IBS patients. Together our results suggest that eosinophils play a role in the pathophysiology of IBS and the mechanisms might be linked to an altered microbiota. Graphical Abstract: Fecal eosinophil‐derived neurotoxin (F‐EDN) levels are correlated to degranulation of eosinophils in the colon of irritable bowel syndrome (IBS) patients.